Study of Paclobutrazol Dosage and Seed Size on Growth and Yield of Porang (Amorphophallus onchophyllus P.) - Hidayah, Sefti Nurul; Hidayat, Ramdan; Triani, Nova (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
The konjac plant (Amorphophallus oncophyllus Prain.) contains high glucomannan with many benefits. Â This experiment aimed to study effect of paclobutrazol dose and seedling size on the growth and yield of konjac plants.Â The research was arranged factorially based on a Completely Randomized Design with two factor.Â The first factor (paclobutrazol dose) consisted of P0: 0.0 g/plant, P1: 0.05 g/plant, P2: 0.10 g/plant, P3: 0.15 g/plant, P4: 0.20 g/plant.Â The second factor (seed size) consisted of U1: 20-50 g/seed, U2: 100-150 g/seed, U3: 200-250 g/seed. Observation parameters included plant height, canopy diameter, stem diameter, stem sturdiness, number of buds, weight and diameter of tubers.Â Results showed that paclobutrazol dose of 0.20 g/plant had a significant effect on stem sturdiness, weight and diameter of the tubers. The maximum of tuber weight obtained by paclobutrazol application of 0.2 g/plant was estimated to be 1,533 g with tuber diameter of 167 mm.Â Small size seed (20-50 g) produced the largest number of buds and did not differ markedly from those of medium size seed (100-150 g).Â Large size seed (200-250 g) produced the best konjac plants in term of canopy diameter, stem sturdiness, weight and diameter of tubers. Â Keywords : Dosage, Konjac, Paclobutrazol, Seed Size, Tuber Size